The Impact of Carbon Tax Law and Green Legal Awareness on The Paris Agreement Compliances With Green Behavior As Mediator - Karim, Abdul; Riskanita, Dinda (Journal of Law, Politic and Humanities, 2025)
Paris Agreement is a global environment legal protection that was ratified by many countries, including Indonesia. Government of Indonesia released Law No. 16 of 2016 as legal formalizes Indonesia's commitment to Paris Agreement. Indonesia also released Law No. 7 of 2021 as legal basis for carbon tax to include the pro-environment tax on Indonesia Tax Regulation. In order to evaluate the correlations between the variables, this study uses a mixed-methods technique that combines quantitative surveys with legal analysis. This normative-empirical study focuses on the effects of carbon tax laws and green legal awareness, analyzing how they affect people's green behavior and subsequent adherence to the goals of the Agreement. Normatively, the study examines the moral and legal foundations of carbon taxes as a climate change mitigation strategy, and empirically, it investigates how well these laws influence public opinion. The Simple Random Sampling method was used for collecting the data through a structured questionnaire to 120 executives in Green Certified Logistic Centre and analyzed by Smart PLS 4.0.9.6. It is argued that a key component of converting legal frameworks into concrete actions is green legal awareness, which includes knowledge and comprehension of environmental laws and rights. This study also suggests that the relationship between carbon tax law, green legal knowledge, and Paris Agreement compliance is mediated by green behavior, which includes ecologically conscious decisions and activities. By looking at this mediating function, the study hopes to shed light on how public awareness and legal frameworks might work together to encourage individual acts that support global climate goals.